Assessment of Failure along Re-Entrant Corner Cracks in Existing RC Dapped-End Connections. Issue 2 (3rd April 2021) - Rajapakse, Chathura; Degée, Hervé; Mihaylov, Boyan
Abstract: Reinforced concrete dapped-end connections are common in existing bridges and represent a critical component of the structure. Due to high stress concentrations in the re-entrant corner of the connection, dapped-ends typically feature inclined corner cracks that occur under service loads. Widening of these cracks due to material degradation and increasing loads can lead to yielding of the dapped-end reinforcement and subsequent failure of the connection. While most of the research devoted to predicting the peak resistance of such dapped-end connections has focused on the strut-and-tie and stress field modelling approaches, there remains a need for mechanical models that facilitate the direct use of on-site measurable data for assessing the strength of the connection. This paper presents the derivation of such a model based on first principles: kinematics, equilibrium and constitutive relationships. The model utilizes measured angles of the inclined crack as an input, and explicitly accounts for kinematic parameters such as the width and the length of the corner crack. A database of 47 tests from the literature featuring variable properties is used to validate the model. It is shown that the proposed approach captures well the peak resistance of dapped-end connections governed by the widening of the crack at the re-entrant corner, leading to an average strength experimental-to-predicted ratio of 1.10 and a coefficient of variation of 8.6%. Furthermore, the model is used to discuss the effect of the angle of the critical corner crack on the peak resistance of the connection.